Toxin production by Bipolaris sorokiniana and its role in determining resistance in wheat genotypes - P. DUREJA; K.D. SRIVASTAVA, M. JAHANI, RASHMI AGGARWAL* (Indian Phytopathology, 2006)
Bipolaris sorokiniana causing spot blotch of wheat produces toxins, which play role in pathogenicity. The isolates of B. sorokiniana differed in their pathogenicity. The profiles of toxin isolated from BS-25 (most virulent isolate) and BS-7 (least virulent isolate) differed on TLC plate; indicating qualitative and quantitative differences. These two isolates were also differentiated on a set of wheat differential lines. Isolate BS-25 showed lowest average infection index (9.6) on genotype Sanghai 4 whereas isolate BS-7 showed 4.9 infection index on the same genotype. With crude toxin symptoms like chlorosis and necrosis on leaf were developed. The toxin from BS-25 produced severe to mild water soaking symptoms on the infiltrated leaf tissue, of Agra local.